Regulating the expression of exercise-induced micro-RNAs and long non-coding RNAs: implications for controlling cardiovascular diseases and heart failure - Yang, Guobiao; Yang, Wanying (Frontiers in Molecular Biosciences, 2025)
The intricate interplay between physical training and non-coding RNAs, specifically microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), has attracted considerable attention in understanding physiological adaptations and pathological conditions. Both miRNAs and lncRNAs are essential modulators of gene expression, influencing various cellular processes, including those related to muscle metabolism, inflammation, and recovery from injury. This review investigates the bifunctional role of miRNAs and lncRNAs in response to physical training, highlighting their involvement in muscle hypertrophy, endurance adaptations, and the modulation of inflammatory pathways. Additionally, we examine how pathological conditions, such as cardiovascular disease, heart failure, can alter the expression profiles of miRNAs and lncRNAs, potentially disrupting the beneficial effects of physical training. The crosstalk between these non-coding RNAs under physiological and pathological states underscores their potential as biomarkers for assessing training responses and therapeutic targets for enhancing recovery and performance. Understanding these interactions may pave the way for novel interventions to optimize health outcomes through tailored physical training programs.